Language Learning Strategies Used by Indonesian Vocational High School English Debate Group - Sugeng Susilo Adi; Frida Unsiah; Riski Nindya Lestari (International Journal of English Linguistics, Literature, and Education (IJELLE), 2019)
This article describes language learning strategies used by vocational high school English debate group. This research used qualitative approach. The data used in this research was in the form of information about language learning strategies.  The researcher used interview as the instrument to collect the data and observation checklist to complete the data of interview. In this study, the researcher only took the three students who were recommended by the English teacher. Three student already chosen were the students who got great achievement such as third winner in Asian Debate Competition. The students used metacognitive strategies by using some strategies like arranging and planning with finding out about language learning, using evaluating learning by self evaluating. The researcher suggest that if they used language learning strategies so they can be a better language learner.